ABNORMAL RETURN AND TRADING VOLUME OF ACTIVITY ANNOUNCEMENT IN PROPERTY TAX AMNESTY IN INDONESIAN - Fadrul Fadrul; Nur Fadjrih Asyik; Mimelientesa Irman; Irena Shannan Jessica; Erwin Febriansyah (Journal of Applied Business and Technology, 2020)
This study aims to analyze the impact of the tax amnesty announcement for 3 periods in Indonesian, namely in period 1 (28 June 2016 30 September 2016), period 2 (1 October 2016-31 December 2016) and period 3 (1 January 2017-31 March 2017). This study included 46 property companies listed on the Indonesian Stock Exchange. The data analysis technique used were event study to calculate the abnormal return and trading volume activity which was paired sample t-test. The results showed that there was no significant difference in abnormal return and trading volume activity before and after the tax amnesty announcement. This indicates that investors as capital market players consider this announcement information does not contain meaningful information for investors, hence, investors in the capital market do not react.